Involvement of Protein Acyltransferase ZDHHC3 in Maintaining Oocyte Meiotic Arrest in Xenopus laevis. Issue 3 (1st September 2016) - Fang, Junshun; Wang, Huawei; Miao, Liyun; Kuang, Xia; Ma, Weirui; Wang, Chao; Zhang, Jian; Xia, Guoliang
Abstract: Fully grown oocytes of most vertebrates are arrested at prophase I of meiosis (G2 arrest). Upon exposure to steroid hormones, oocytes resume meiotic process, also called G2/M transition. The G protein-signaling pathway has been shown to play essential roles in the meiotic arrest at G2 phase. Previously, we showed that long chain fatty acyl-coenzyme A synthetase acsl1b was required for maintaining the meiotic arrest in Xenopus Acsl1b presumably synthesizes palmitoyl-coenzyme A that can be utilized by acyltransferases to modify proteins essential for the G2 arrest. In the present study, we report that protein acyltransferase ZDHHC3 functions downstream of acsl1b to maintain oocyte meiotic arrest. Depletion of maternal ZDHHC3 RNA in oocytes reduces the progesterone threshold to promote G2/M transition from 2 to 0.01 μM. As expected, Gs alpha palmitoylation level is greatly decreased in ZDHHC3 -depleted oocytes. Furthermore, we mapped ZDHHC3 palmitoylation sites in Gs alpha and showed that palmitoylation-deficient Gs alpha failed to arrest oocytes at G2. We also identified a critical residue in ZDHHC3 critically required for its palmitoylation activity toward Gs alpha. Taken together, ZDHHC3 is a key acyltransferase to palmitoylate proteins in order to maintain G2 arrest in Xenopus oocytes.